Determination of Sinomenine in Cubosome Nanoparticles by HPLC Technique. (5th February 2015) - Zhou, Yanfang; Guo, Chunlian; Chen, Hongying; Zhang, Yudai; Peng, Xinsheng; Zhu, Ping
Abstract : We applied HPLC technique to quantitatively analyze sinomenine in cubosome nanoparticles. The chromatographic method was performed by using an isocratic system. The mobile phase was composed of methanol-PBS(pH6.8)-triethylamine (50 : 50 : 0.1%) with a flow rate of 1 mL/min; the detection wavelength was at 265 nm. Sinomenine can be successfully separated with good linearity (the regression equation isA = 10 835 C + 1058 ;R 2 = 1.0 ) and perfect recovery (102.2%). The chromatograph technique was proper for quality control of sinomenine in cubosome nanoparticles.